The role of loyal workers enhance market share center the human resource management strategies / field research in cellular telecommunication companies - صيهود علي موات; ستار رشا عبدالخالق (Journal of Economics and Administrative Sciences, 2017)
The problem for the search to identify the role of loyal workers through (emotional loyalty, moral loyalty, continued loyalty) in enhancing the market share of the corporate center the human resource management strategies, namely (selection, training and development, and performance evaluation, and returns the system) for the parent company of cellular Allotsalat in Baghdad , and show the importance of research through the benefit to the company, through the importance of the search results, it draws the attention of decision-makers and those in charge of managing these human resources on the importance of those resources and work to develop them and keep them in order to increase their loyalty towards their organization and then growth and increase market share for the company. as well as the staff working as taking place on the important and sensitive category because they deal daily, even on holidays and special occasions with large numbers of beneficiaries of their services and who vary their needs from one person to another, and it was the goal of search Hothdid concept and the importance and the role of the loyalty of workers to increase market share for companies through a resource management strategies Alepeshrah.oachtbar correlation relationship between the loyalty of employees and human resource management strategies. And test the correlation between the strategies of human resource management and market share for the company. As well as the correlation test (direct and indirect) between the loyalty of employees and market share through the strategies of human resources management .omarafh mutual impact between the variables of research and of the loyalty of employees and strategies of human resource management and market share for the company. the statement of proposals to ensure the successful activation of the role of loyal workers in enhancing the market share of the corporate center the strategies of human resources management, in line with the research methodology has been formulated hypotheses to refer to the possibility of the application of the scheme Search is there a significant correlation between the loyalty of employees and market share relationship, and whether there is a correlation spirits between the strategies of human resources management and market share and whether there is a significant effect of the loyalty of employees in market share, as well, is there a significant effect of the strategies of human resources management in market share, and because the service sector has become very important in the present time through his contribution. along with other sectors in the construction and development of society and increased well-being, the research community Zain Iraqna and Asia-Cell Telecom room hypotheses to test by taking a simple random sample, and through the design of a questionnaire form a basic tool included on (70) items to collect the raw data from the employees of these two companies, was the sample (50) Show of Asiacell and (50) Show Zain Iraq, and then were collected samples to form the size of a sample (100) Show, in order to address these data have been used a lot of ways statistical methods (such as measuring frequencies, ratios and the severity of the answer, measuring the average deviation standard, coefficient of variation, measuring the link power and influence, a study analyzing the track, and then use spss program, Excel and Matlab program for the analysis of the results). By measuring the research, diagnosis and testing of the link and influence, including relationships variables, research found a set of conclusions was Pinha.ugod relationship between loyalty and market share and the existence of a relationship impact on market share, directly and indirectly through the dimensions of strategic management Almwardalepeshrah, it has been a group setting of recommendations based on the findings of this research findings, as well as suggest some future studies that promote aspects of these issues, including the work on expanding this research to include variables new dimensions covered no such research, which has a direct role or is Mbacraly enhance market share for organizations